The methods of therapy of children suffering from cerebral palsy - Stecko, Monika Joanna; Wawryków, Agata; Korabiusz, Katarzyna; Kordek, Agnieszka; Fabian - Danielewska, Anna; Wilczyńska, Agnieszka; Janik, Inga; Maciejewska, Martyna (Journal of Education, Health and Sport, 2018)
Cerebral palsy and methods of therapy that can be applied in the process of rehabilitation of children were described in this article. Cerebral palsy is a motor syndrome caused by permanent damage to the structures of central nervous system in the prenatal, perinatal or postnatal period [1]. Cerebral palsy is a complex therapeutic problem. It is not possible to cure it completely, therefore, the main goal is alleviation of pain to make the child as independent in everyday life as possible [2]. Nowadays, rehabilitation of children suffering from cerebral palsy is based on the methods of neurodevelopmental rehabilitation, which are the most effective and more child-friendly. These methods include, among others, Vojta and NDT-Bobath method. Additional methods that can be applied while supporting the development of children suffering from cerebral palsy are sensory integration method and MEDEK method. If appropriate and comprehensive rehabilitation shall be initiated at early stage in children suffering from cerebral palsy, the chance for achievement of proper mobility in the future will be bigger [3]. The effects of therapy depend on the type of damage, regularity of therapy. Therapeutic program must be selected individually to every child after thorough diagnosis and observation [2,4].